2000
DOI: 10.1159/000021729
|View full text |Cite
|
Sign up to set email alerts
|

Allocare in a Nocturnal Primate: Data on the Spectral Tarsier, Tarsius spectrum

Abstract: Non-maternal infant care in many of the small-bodied New World primate species has been hypothesized by some researchers to be related to the high infant/adult weight ratio found in these species. The spectral tarsier, Tarsius spectrum, an Old World primate, has one of the highest infant/adult weight ratios of any primate, with infants weighing between 20–33% of adult weight at birth. On the basis of the hypothesized relationship between allocare and the infant/adult weight ratio, it is predicted that the spec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
18
0
1

Year Published

2005
2005
2019
2019

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(20 citation statements)
references
References 44 publications
1
18
0
1
Order By: Relevance
“…This happens in some other species, such as killer whales (Bigg et al . ), bottlenose dolphins (Lusseau ), Atlantic spotted dolphins ( Stenella frontalis , Weinpress and Herzing ), spectral tarsiers ( Tarsius tarsier , Gursky ), and black snub‐nosed monkeys ( Rhinopithecus bieti , Xiang et al . ).…”
Section: Discussionmentioning
confidence: 99%
“…This happens in some other species, such as killer whales (Bigg et al . ), bottlenose dolphins (Lusseau ), Atlantic spotted dolphins ( Stenella frontalis , Weinpress and Herzing ), spectral tarsiers ( Tarsius tarsier , Gursky ), and black snub‐nosed monkeys ( Rhinopithecus bieti , Xiang et al . ).…”
Section: Discussionmentioning
confidence: 99%
“…Tarsiers are quite small primates (ca. 100 g) that produce single infants who weigh as much as 22% of the mother's body mass at birth (Gursky 2000 ) . Like titi and owl monkeys, tarsiers are predominantly pair-living, though not as exclusively as the former two taxa.…”
Section: Strepsirrhines and Tarsiersmentioning
confidence: 99%
“…Like titi and owl monkeys, tarsiers are predominantly pair-living, though not as exclusively as the former two taxa. Care behavior is occasionally shown by subadults of both sexes and adult males, but it is the subadult females that are most involved (Gursky 2000 ) . Care takes mainly the form of grooming, playing, and staying in proximity to the infant, but only rarely of carrying it, since infants are usually parked.…”
Section: Strepsirrhines and Tarsiersmentioning
confidence: 99%
“…While it would be inappropriate to make sweeping generalizations on mating systems and social organization on the basis of data collected in this study, we found a marked difference in behavior between captive and wild T. syrichta. In captivity, T. syrichta exhibited some level of limited allocare, similar to that shown by T. spectrum [Gursky, 2000]. In contrast, previous studies of wild groups showed that this species either exhibits monogamy or some level of a noyau mating system [Neri-Arboleda, 2001].…”
Section: Semi-captive Densities and Behaviormentioning
confidence: 60%